Perspectives of ammunition users on the use of lead ammunition and its potential impacts on wildlife and humans. Issue 3 (3rd June 2019) - Newth, Julia L.; Lawrence, Alice; Cromie, Ruth L.; Swift, John A.; Rees, Eileen C.; Wood, Kevin A.; Strong, Emily A; Reeves, Jonathan; McDonald, Robbie A.
Abstract: Recent national and international policy initiatives have aimed to reduce the exposure of humans and wildlife to lead from ammunition. Despite restrictions, in the UK, lead ammunition remains the most widespread source of environmental lead contamination to which wildlife may be exposed. The risks arising from the use of lead ammunition and the measures taken to mitigate these have prompted intense and sometimes acrimonious discussion between stakeholder groups, including those advancing the interests of shooting, wildlife conservation, public health and animal welfare. However, relatively little is known of the perspectives of individual ammunition users, despite their role in adding lead to the environment and their pivotal place in any potential changes to practice. Using Q‐methodology, we identified the perspectives of ammunition users in the UK on lead ammunition in an effort to bring forward evidence from these key stakeholders. Views were characterised by two statistically and qualitatively distinct perspectives: (a) Open to change —comprised ammunition users that refuted the view that lead ammunition is not a major source of poisoning in wild birds, believed that solutions to reduce the risks of poisoning are needed, were happy to use non‐lead alternatives and did not feel that the phasing out of lead shot would lead to the demise of shooting; and (b) Status quo —comprised ammunition users who did not regard lead poisoning as a major welfare problem for wild birds, were ambivalent about the need for solutions and felt that lead shot is better than steel at killing and not wounding an animal. They believed opposition to lead ammunition was driven more by a dislike of shooting than evidence of any harm. Adherents to both perspectives agreed that lead is a toxic substance. There was consensus that involvement of stakeholders from all sides of the debate was desirable and that to be taken seriously by shooters, information about lead poisoning should come from the shooting community. This articulation of views held by practitioners within the shooting community presents a foundation for renewing discussions, beyond current conflict among stakeholder and advocacy groups, towards forging new solutions and adaptation of practices. A freePlain Language Summary can be found within the Supporting Information of this article. Abstract : A freePlain Language Summary can be found within the Supporting Information of this article.